The Relationship between Family Support and Smoking Behavior in Adolescents in the Donggala Health Center Work Area, Donggala Regency, Central Sulawesi - Ratna Devi; Hayati Palesa; Warihan Unok; Mayu Sanlia Samadani (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Adolescence is a time to determine choices about what to do, including smoking behavior. Smoking is an action that is considered normal by today's society, even though it has high health risks. Purpose: This study aims to determine the relationship between emotional support and assessment/appreciation support on smoking behavior in adolescents in the Donggala Health Center work area. Smoking behavior in adolescents is a serious health problem that can have long-term impacts on their well-being. Method: This study is a quantitative study with a cross-sectional approach. The sample consisted of 73 adolescents who actively smoke in the area. Data were collected through a questionnaire that measured the level of emotional support and assessment support and adolescent smoking behavior. Results: This study shows a significant relationship between emotional support and smoking behavior, (p <0.05), as well as assessment support and smoking behavior in adolescents (p <0.05). This study highlights the important role of family support in preventing smoking behavior in adolescents. Emotional support and positive assessment from the family can help adolescents make healthier decisions about smoking. Conclusion: This study concludes that the existence of other factors that influence smoking behavior indicates the importance of a comprehensive prevention approach, involving various parties such as educational institutions, communities, and further research, to develop effective prevention strategies for adolescents.